Lipedema associated with Skin Hypoperfusion and Ulceration: Soft Tissue Debulking Improving Skin Perfusion - Alshomer, Feras; Lee, Seok Joon; Kim, Yeongsong; Hong, Dae Won; Pak, Changsik John; Suh, Hyunsuk Peter; Hong, Joon Pio (Archives of Plastic Surgery, 2024)
Lipedema is a progressive connective tissue disease with enlargement of adipose tissue, fibrosis, fluid collection, and dermal thickening. Herein, we present a case of lipedema associated with skin hypoperfusion and ulceration in which soft tissue debulking with liposuction improved patients' symptoms. A 39-year-old female presented with asymmetric progressive initially unilateral lower limb swelling with severe pain with subsequent skin ulceration. Conservative management failed to improve her condition. After excluding other causes and detailed radiologic investigation, lipedema was diagnosed with an associated impaired skin perfusion. Trial of local wound care and compression therapy failed to improve the condition. Subsequent soft tissue debulking with circumferential liposuction and ulcer debridement and immediate compression showed dramatic improvement of the symptoms and skin perfusion. The unique nature of this case sheds light on lipedema as a loose connective tissue disease. Inflammation and microangiopathies explain the associated pain with hypoperfusion and ulceration being quite atypical and in part might be related to the large buildups of matrix proteins and sodium contents leading to fragility in microvessels with frequent petechiae and hematoma and subsequent tissue ischemia. Conservative measures like compression therapy plays a significant role in disease course. Surgical debulking with liposuction was shown to be efficacious in reducing the soft tissue load with improvement in limb pain, edema, circumference, and skin perfusion that was seen in our patient. Lipedema is a frequently misdiagnosed condition with disabling features. Skin involvement in lipedema with potential hypoperfusion was shown and it requires further investigation.
Keywords: lipedema; hypoperfusion; liposuction; ulcer